FROM SCIENTIFIC LITERACY TO SOCIOEMOTIONAL LITERACY: COMPLEMENTARY APPROACHES STUDENT EDUCATION - Vitor Rodrigues Santos, José; Félix Seabra, Fernanda; Barboza Morais, Jociela; Liziane Farias Maia de Araújo, Yzila; Batista Santos, Ivanete; Maris Versuti, Fabiana; Maria Santos Gouw, Ana; Raíssa Nascimento Pereira, Kethlyn; Santos Mota, Helenadja (Revista Gênero e Interdisciplinaridade, 2026)
This work presents a systematic review of the last decade that sought to analyze gaps left by Scientific Literacy (CL), as identified in the guidelines of the National Common Curricular Base (BNCC), which can be complemented/integrated by Socio-Emotional Literacy (LS). The methodology employed is rooted in exploratory research, underpinned by a qualitative approach, and is informed by a bibliographic mapping of studies published between 2014 and 2024 in the Brazilian Digital Library of Theses and Dissertations (BDTD) and the Scientific Electronic Library Online (Scielo). The theoretical framework underpinning the study encompasses research contributions by Bertotti (2021), De Pauli (2023), Paranhos (2017) and Abed (2016). The investigation revealed that Scientific Literacy holds promise in the training of critical individuals; however, it exhibits deficiencies during its implementation that impede students from developing competencies that integrate diverse emotional and cognitive domains. Consequently, Socio-Emotional Literacy addresses these deficiencies, thereby facilitating the completion of students’ training.